2021
DOI: 10.3390/cells10051212
|View full text |Cite
|
Sign up to set email alerts
|

Liver Fibrosis during Antiretroviral Treatment in HIV-Infected Individuals. Truth or Tale?

Abstract: After the introduction of antiretroviral treatment (ART) back in 1996, the lifespan of people living with HIV (PLWH) has been substantially increased, while the major causes of morbidity and mortality have switched from opportunistic infections and AIDS-related neoplasms to cardiovascular and liver diseases. HIV itself may lead to liver damage and subsequent liver fibrosis (LF) through multiple pathways. Apart from HIV, viral hepatitis, alcoholic and especially non-alcoholic liver diseases have been implicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 137 publications
0
18
0
1
Order By: Relevance
“…Liver disease is one of the major causes of morbidity and mortality in PLWH [ 17 , 18 ]. As far as liver fibrosis is concerned, available studies report that its prevalence in HIV-infected patients ranges from 1.4% to 63% according to different populations [ 20 , 28 , 29 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Liver disease is one of the major causes of morbidity and mortality in PLWH [ 17 , 18 ]. As far as liver fibrosis is concerned, available studies report that its prevalence in HIV-infected patients ranges from 1.4% to 63% according to different populations [ 20 , 28 , 29 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently available antiretroviral drugs have dramatically changed the landscape of HIV infection, reducing mortality for any reason but increasing the impact of aging-related comorbidities. However, even if many controversies still exist, the potential impact of some antiretroviral drugs in mid- and long-term liver abnormalities is known, in particular due to first-generation NRTIs, such as AZT and PIs [ 17 , 38 ]. In our study, we observed an effect of longer cumulative atazanavir exposure on liver stiffness measurements by TE, according to previous literature data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is estimated that each year of NRTI treatment may add an 11% risk to NAFLD ( 206 ). However the progression of NAFLD to liver fibrosis is a rare and lengthy process ( 208 ). The metabolic and inflammatory mechanisms generated by HIV and ART are depicted in the Figure 2 .…”
Section: Hiv and Hbv Role In Nafld Pathogenesis And In The Breakdown ...mentioning
confidence: 99%